2008
DOI: 10.1080/01612840802274933
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Psychiatric Disorders among Older Adult Recovering Pathological Gamblers

Abstract: The proliferation of state lotteries and casinos has led to an increased participation in gambling and its associated problems. Older retired adults have more opportunities to gamble and available funds than other demographic groups. For these reasons, older adults may constitute a special risk group for pathological gambling. Because substance misuse, mood, anxiety, and personality disorders are common in problem and pathological gamblers, we sought to examine rates of comorbid psychiatric disorders in 40 old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 19 publications
1
33
0
2
Order By: Relevance
“…A recent meta-analysis revealed that the mean prevalence of ADHD in treatment-seeking problem gamblers is 9.3 % (Dowling et al 2015). There was, however, moderate heterogeneity between the studies, with estimates ranging from 1.3 to 20.0 % (Dannon et al 2006;Grall-Bronnec et al 2011;Kerber et al 2008;Specker et al 1995). Moreover, Specker et al (1995) reported that while 20 % of problem gamblers met criteria for ADHD using an operationalized diagnostic interview, an additional 18 % missed threshold criteria by only one item.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent meta-analysis revealed that the mean prevalence of ADHD in treatment-seeking problem gamblers is 9.3 % (Dowling et al 2015). There was, however, moderate heterogeneity between the studies, with estimates ranging from 1.3 to 20.0 % (Dannon et al 2006;Grall-Bronnec et al 2011;Kerber et al 2008;Specker et al 1995). Moreover, Specker et al (1995) reported that while 20 % of problem gamblers met criteria for ADHD using an operationalized diagnostic interview, an additional 18 % missed threshold criteria by only one item.…”
Section: Introductionmentioning
confidence: 91%
“…Problem gambling has been consistently associated with a range of comorbid psychiatric conditions, including personality disorders, alcohol and other substance use disorders, mood disorders, anxiety disorders, and other impulse control disorders (Dowling et al , 2015Lorains et al 2011). There is also emerging evidence of a relationship between problem gambling and Attention Deficit Hyperactivity Disorder (ADHD) (Breyer et al 2009;Dannon et al 2006;Dowling et al 2015;Faregh and Derevensky 2011;Grall-Bronnec et al 2011;Kerber et al 2008;Specker et al 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Older age can bring with it a decline in cognitive functions that may make it harder to control one's gambling [28]. Research has also shown that comorbidity of problem gambling and mental illness was significantly more common among adults aged 55 and older when compared to the overall rate [27]. Financial constraints of being on limited or fixed incomes can also exacerbate the negative consequences of gambling losses for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Problem gambling has been associated closely with negative emotional states such as depression and anxiety [25,26] and lower cognitive function [27]. Older age can bring with it a decline in cognitive functions that may make it harder to control one's gambling [28].…”
Section: Introductionmentioning
confidence: 99%
“…Other co-morbidities could also cause impairments on pathological gamblers' decision-making processes. For instance, it has been reported that ADHD, depression and anxiety, which are frequently associated with gambling addiction (e.g., Kerber et al 2008), could alter performance on the IGT (ADHD: e.g., Bubier and Drabick 2008;depression: e.g., Cella et al 2010;anxiety: e.g., Mueller et al 2010). In this study, potential confounding effects of ADHD, anxiety and depression on decision-making were controlled.…”
Section: Introductionmentioning
confidence: 99%